Death on the Pont Noir - Magson, Adrian (London Allison & Busby Limited, 2013)
1963 - Picardie, Northern France. Following an inexplicable ramming and gun attack on a Citroen DS in the middle of open countryside, and a bar brawl involving a group of drunken Englishmen, Inspector Lucas Rocco finds himself drawn into what has all the hallmarks of a plot to assassinate President Charles de Gaulle - one of many made on the French leader's life. But why are English gangsters working for a well-known pair of London gangland twins involved, and who has set fire to an ex-army truck with a body inside? And why have those who made a previous abortive attack on the president suddenly disappeared? Rocco finds himself once more pulled several ways while attempting to investigate a seemingly disconnected series of events - only this time, he's accused of taking bribes and even suspected of being part of the assassination plot himself.
Keywords: France -- Private investigators